PENINGKATAN KETERAMPILAN BERCERITA DENGAN MENGGUNAKAN MEDIA WAYANG KARTUN PADA SISWA VII A SMP NEGERI 4 PURBALINGGA KABUPATEN PURBALINGGA TAHUN PELAJARAN 2017/2018 - Nia Ulfa Martha; Vera Krisnawati (BAHASTRA, 2018)
This study aims to improve the skills of telling students VII A SMP Negeri 4 Purbalingga after using wayang cartoon media. The method of this research is descriptive quantitative and qualitative descriptive. The research design used is classroom action research. Classroom action research process includes cycle I and cycle II. The results showed an increase in storytelling skills. The average value and study completeness has increased significantly. Cycle I 61,87 sufficient category and cycle II 76,31 good category. Observations on student attitudes also indicate a better improvement. Students are more enthusiastic about learning and learning becomes fun.